(3cQI GdSdI ddfGTFjfs - (3ahRj GMeO Gejfs ((3GdGScfOQjIs (3GdecJHI GdeUQjI ddWHGYI h GdfTQh GdJhRjYs, 2004)
(3jbOe GdeHGOF GdMQcjI GdCSGSjI GdJj JJCSS YdjgG eeGQSI GdfGTFjf ddYHI hjJVef WQjbI JYdje h JfejI GdegGQGJ h GdNWW GdgLhejI h GdOaGYjI h jJUOi dWQjbI bjGS h Jbjje ddfGTFf(B.s